E-Learning Evaluation Based on Context, Input, Process, and Product (CIPP) - John Friadi; Asro; Arina Luthfini Lubis; Dodi P. Yani; Suroto; Ansyar Bora; Alfiyandri (Jurnal Penelitian Pendidikan IPA, 2024)
The development of internet-based information technology has had an impact on many aspects of human life, including education. Online learning is made possible by the learning paradigm in the industrial era 4.0. During the COVID-19 pandemic, many universities implemented online learning methods using E-Learning, in line with government recommendations to implement health protocols to break the chain of the COVID-19 virus, such as wearing masks, washing hands and maintaining distance. The Faculty of Engineering, Batam University has used e-learning for learning during the pandemic and continues after the pandemic, but its implementation has never been evaluated. The aim of this research is to assess the context, input, process and product (CIPP) of e-learning at the Faculty of Engineering, Batam University. This research uses a quantitative and qualitative approach (mixed research) by distributing questionnaires to lecturers and students of study programs within the Faculty of Engineering, Batam University. Based on research conducted by evaluating E-Learning from the context aspect, both lecturers and students gave very good responses so it needs to be maintained. Furthermore, from the input aspect it provides a very good response, therefore it needs to be maintained and improved. The response from lecturers for the process aspect is in the very good category, while the response from students is in the good category, so the process element needs to be improved. Assessment of the product aspect shows that E-Learning at the Faculty of Engineering, Batam University must be improved.